Current perspectives in the management of sepsis and septic shock - Chiscano-Camón, Luis; Ruiz-Sanmartin, Adolf; Bajaña, Ivan; Bastidas, Juliana; Lopez-Martinez, Rocio; Franco-Jarava, Clara; Gonzalez, Juan José; Larrosa, Nieves; Riera, Jordi; Nuvials-Casals, Xavier; Ruiz-Rodríguez, Juan Carlos; Ferrer, Ricard (Frontiers in Medicine, 2024)
Within patients with sepsis, there exists significant heterogeneity, and while all patients should receive conventional therapy, there are subgroups of patients who may benefit from specific therapies, often referred to as rescue therapies. Therefore, the identification of these specific patient subgroups is crucial and lays the groundwork for the application of precision medicine based on the development of targeted interventions. Over the years, efforts have been made to categorize sepsis into different subtypes based on clinical characteristics, biomarkers, or underlying mechanisms. For example, sepsis can be stratified into different phenotypes based on the predominant dysregulated host response. These phenotypes can range from hyperinflammatory states to immunosuppressive states and even mixed phenotypes. Each phenotype may require different therapeutic approaches to improve patient outcomes. Rescue strategies for septic shock may encompass various interventions, such as immunomodulatory therapies, extracorporeal support (e.g., ECMO), or therapies targeted at specific molecular or cellular pathways involved in the pathophysiology of sepsis. In recent years, there has been growing interest in precision medicine approaches to sepsis and phenotype identification. Precision medicine aims to tailor treatments to each individual patient based on their unique characteristics and disease mechanisms.